Handbook of nonlinear partial differential equations - q; 9 (Boca Raton, FL : CRC Press, 2012)
"Updated and expanded, this popular handbook provides a catalog of 2,100 nonlinear PDEs and their solutions. With nearly 400 pages of new and updated material, this edition contains over 500 nonlinear PDEs with solutions and many new nonlinear systems of PDEs with solutions.In the first half of the book, numerous new and nonlinear systems of PDEs are described with a focus on equations containing one or more arbitrary parameters. The authors cover equations that arise in heat transfer, wave theory, nonlinear mechanics, hydrodynamics, gas dynamics, plasticity theory, nonlinear optics, theoretical physics, differential geometry, control theory, biology, and other fields. The second half of the book presents the exact methods used for solving these types of equations. The authors explore classical methods and some recent developments, along with examples that illustrate applications of the methods. "--
"PREFACE TO THE NEW EDITION The Handbook of Nonlinear Partial Differential Equations, a unique reference for scientists and engineers, contains over 3,000 nonlinear partial differential equations with solutions, as well as exact, symbolic, and numerical methods for solving nonlinear equations. First, second, third, fourthand higherorder nonlinear equations and systems of equations are considered. Equations of parabolic, hyperbolic, elliptic, mixed, and general types are discussed. A large number of new exact solutions to nonlinear equations are described. In total, the handbook contains several times more nonlinear PDEs and exact solutions than any other book currently available. In selecting the material, the authors gave the highest priority to the following fivemajor types of equations: - Equations that arise in various applications (heat and mass transfer theory, wave theory, nonlinear mechanics, hydrodynamics, gas dynamics, plasticity theory, nonlinear acoustics, combustion theory, nonlinear optics, theoretical physics, differential geometry, control theory, chemical engineering sciences, biology, and others). - Equations of general form that depend on arbitrary functions; exact solutions of such equations are of principal value for testing numerical and approximate methods. - Equations forwhich the general solution or solutions of quite general form, with arbitrary functions, could be obtained. - Equations that involve many free parameters. - Equations whose solution is reduced to solving linear partial differential equations or linear integral equations. The second edition has been substantially updated, revised, and expanded. More than 1,500 new equations with exact solutions, as well some methods and many examples, have been added"--
Includes bibliographical references and index.
Keywords: Differential equations, Nonlinear -- Numerical solutions; Nonlinear mechanics -- Mathematics